From London to Barcelona: 18 years of contributions from ICSEI - F. Javier Murillo (Universidad Autónoma de Madrid, 2015)
Between January 2 and 5, 2005, the XVIII Meeting of the International Congress for School Effectiveness and Improvement was held in Barcelona. It was, then, one more step in the long process begun in mid-1987, when a group of scholars from seven countries fostered the organization of a meeting between researchers to address the issue of School Effectiveness. This first congress was organized in 1988 in London under the auspices of the Institute of Education at the University of London and led by Dale Mann, first director of the National Council for Effective Schools.